Brand engagement without brand ownership: a case of non-brand owner community members. Issue 2 (13th February 2019) - Kumar, Jitender; Nayak, Jogendra Kumar
Abstract : Purpose: Considering brand ownership as a cause of concern, this paper aims to propose a conceptual model portraying brand engagement as a function of members' brand psychological ownership (BPO) and value-congruity and to investigate the effect of brand engagement on brand attachment and brand purchase intentions. Design/methodology/approach: Data were collected from 275 brand community members who do not own the brand. Six different brand communities were shortlisted and offline events were targeted. For testing the hypothesised relationships, the authors used structural equation modelling. Findings: The results indicate that BPO and value-congruity positively influence the brand engagement of the members, which further influences the brand attachment and brand purchase intentions. It is also observed that brand attachment mediates the effect of brand engagement on brand purchase intentions. Research limitations/implications: The primary limitation of this paper is the research context, which needs to be further replicated. The specific customer-segment approach of the study adds a new direction to the scope of brand engagement in the brand management domain. Practical implications: The study shows that brand managers need to expand their focus from existing brand customers to non-customers as brand engagement subjects because the non-brand owners can also experience brand attachment and develop intentions to purchase the brand, if engaged. Originality/value: The study endorses the role of psychological ownership theory in brand engagement research; explores the feasibility of brand engagement among "non-owner community members"; highlights the role of their engagement in enhancing attachment towards the brands and purchase intentions; and sheds light on the blurred boundaries between brand engagement and brand attachment.